2021
DOI: 10.1016/j.arthro.2021.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Conclusive Evidence of the Benefit of Biologic Augmentation in Core Decompression for Nontraumatic Osteonecrosis of the Femoral Head: A Systematic Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…There is an increasing number of elderly patients undergoing hip arthroplasty for the treatment of osteoarthritis and/or osteonecrosis of the femoral head (ONFH) with unbearable persistent pain. 1 It was reported that the annual incident rate of total hip arthroplasty increased from 15.2/100,000 in 2010 to 22.3/100,000 in 2018 in Korea, showing the same increased tendency as reports from Western countries. 2 Previous studies have reported that approximately 27% of patients developed chronic postsurgical pain (CPSP) after hip arthroplasty.…”
Section: Introductionmentioning
confidence: 69%
“…There is an increasing number of elderly patients undergoing hip arthroplasty for the treatment of osteoarthritis and/or osteonecrosis of the femoral head (ONFH) with unbearable persistent pain. 1 It was reported that the annual incident rate of total hip arthroplasty increased from 15.2/100,000 in 2010 to 22.3/100,000 in 2018 in Korea, showing the same increased tendency as reports from Western countries. 2 Previous studies have reported that approximately 27% of patients developed chronic postsurgical pain (CPSP) after hip arthroplasty.…”
Section: Introductionmentioning
confidence: 69%
“…Till date, however, no statistically signi cant differences in the radiological progression of necrosis and the rate of conversion to arthroplasty, as well as PROM between surgical procedures regarding CD, have been reported 12,13,17,19,21,22 . Only cell therapy combined with CD has shown relatively superior outcomes regarding the radiological progression of ON 11,12,23−27 .…”
Section: Discussionmentioning
confidence: 99%
“…The femoral head usually develops into secondary arthritis when it collapses [ 4 ]. Core decompression (CD) is a commonly used procedure for treating femoral head necrosis despite some controversy; it is a simple procedure that treats ONFH by drilling into the necrotic area of the femoral head [ 5 8 ]. The theoretical advantage of CD is in relieving the pain by reducing venous congestion and bone marrow pressure.…”
Section: Introductionmentioning
confidence: 99%